Insights into the activation mechanism of class I HDAC complexes by inositol phosphates - Peter J. Watson (Nature Portfolio, 2016)
Class I histone deacetylase complexes can be activated by inositol phosphates. Here, the authors investigate the stereochemical requirements for activation; use the crystal structure to understand substrate recognition, and suggest an entropically driven mechanism of allostery.